Analisis Harga, Kualitas Produk, Citra Merek Dan Keputusan Pembelian Produk Smartphone Xiaomi - Listiana Listiana; Nur Aida (Jurnal Pamator : Jurnal Ilmiah Universitas Trunojoyo, 2021)
This study aims to determine the effect of price variables, product quality and brand image on purchasing decisions for Xiaomi smartphones and to find out the role of brand image as a mediating variable between price and product quality on purchasing decisions for Xiaomi smartphones. The study population was users or had used Xiaomi in the Pasuruan area with a total sample size of 97 with a purposive sampling method and analysis was carried out with the SmartPLS 3 application. All research indicators have a loading factor above 0.7 and all research indicators have AVE 0.5. The reliability of the data was tested because it had a Cronbach Alpha value and a composite reliability 0.7. The predicted relevance value is high with Q2 0.00 so that the research is feasible. The results of the study concluded that the price had a positive but insignificant effect on purchasing decisions. Product quality and brand image have a positive and significant effect on purchasing decisions, product quality has a positive and significant effect on brand image, prices have a positive but insignificant effect on brand image. For mediation analysis, it is concluded that brand image is a potential moderation between price and purchase decision. branding is a quasi-moderation for product quality to influence purchasing decisions. The NFI value is 0.807, which means that the model is fit because it is close to unity.